Peranan Alokasi Dana Desa Dalam Pengembangan wilayah di Desa Pasi Mesjid Kecamatan Meureubo Kabupaten Aceh Barat - Dar Kasih (ICODEV: Indonesian Community Development Journal, 2023)
This article discusses the role of Village Fund Allocation (ADD) in Regional Development in Pasi Masjid Village. This writing aims to determine the impact of utilizing Village Fund Allocations in the development of rural areas in the last 5 years. The analytical method used in this study is a qualitative method consisting of indicators in this study namely APBDesa Planning, Fulfillment of Basic Needs, Institutional Strengthening, Increasing Village Potential, Infrastructure Improvement and Development of Rural Areas. The research was conducted in Pasi Masjid Village, Meurebo District, West Aceh Regency with a total of 15 respondents. The results of this study prove that the application of Village Fund Allocation has been directed at the physical and non-physical sectors so that the implementation of Village Fund Allocation Planning, Fulfillment of Basic Needs, Institutional Strengthening, Infrastructure Improvement and Rural Area Development has been carried out effectively in Pasi Masjid Village, Meureubo Regency. However, in the village of Pasi Masjid, it still requires optimizing the roles and functions of social institutions, improving rural infrastructure and improving the functioning of existing economic institutions in the village through increasing Village Fund Allocations.